Does a rising school climate lift all boats? Differential associations of perceived climate and achievement for students with disabilities and limited English proficiency. (December 2018) - Sanders, Steven M.; Durbin, James M.; Anderson, Bart G.; Fogarty, Laura M.; Giraldo-Garcia, Regina J.; Voight, Adam
Previous research studies show that a positive school climate is associated with desirable academic outcomes for youth. In the United States, students with disabilities and English language learner (ELL) students are particularly at-risk for poor academic outcomes and therefore more in need of interventions to support their academic development. The present study examined whether school climate has a differential association with academic achievement for these at-risk students compared to their peers, which would suggest that school climate has the effect of reducing or widening achievement gaps based on disability and language. For students at all levels, the main effects of perceived school climate and disability status on mathematics and reading achievement were statistically significant controlling for race/ethnicity, gender, and grade. The results of this study have numerous implications for school psychology practice. Our findings suggest that a positive school climate is associated with higher achievement for all students at all levels in both mathematics and reading, school psychologists should consider school climate improvement as part of their mandate.